Push-Pull Derivatives Based on 2,4 '-Biphenylene Linker with Quinoxaline, [1,2,5]Oxadiazolo[3,4-B]Pyrazine and [1,2,5]Thiadiazolo[3,4-B]Pyrazine Electron Withdrawing Parts - Verbitskiy, Egor V; le Poul, Pascal; Bureš, Filip; Achelle, Sylvain; Barsella, Alberto; Kvashnin, Yuriy A; Rusinov, Gennady L; Charushin, Valery N (MDPI, 2022)
A series of novel V-shaped quinoxaline, [1,2,5]oxadiazolo[3,4-b]pyrazine and [1,2,5]thiadiazolo[3,4-b]pyrazine push-pull derivatives with 2,4 '-biphenylene linker were designed and their electrochemical, photophysical and nonlinear optical properties were investigated. [1,2,5]Oxadiazolo[3,4-b]pyrazine is the stronger electron-withdrawing fragment as shown by electrochemical, and photophysical data. All compounds are emissive in a solid-state (from the cyan to red region of the spectrum) and quinoxaline derivatives are emissions in DCM solution. It has been found that quinoxaline derivatives demonstrate important solvatochromism and extra-large Stokes shifts, characteristic of twisted intramolecular charge transfer excited state as well as aggregation induced emission. The experimental conclusions have been justified by theoretical (TD-)DFT calculations.
Push-pull deriváty obsahující 2,4 '-bifenylenový linker a chinoxalin, [1,2,5]oxadiazolo[3,4-b]pyrazin a [1,2,5]thiadiazolo[3,4-b]pyrazin jako elektronakceptorní část
Keywords: furazanopyrazine; [1; 2; 5]thiadiazolo[3; 4-b]pyrazine; quinoxaline; donor-acceptor systems; twisted intramolecular charge transfer; furazanopyrazin; thiadiazolopyrazin; chinoxalin; donor-acceptorový systém